‘Pets provide meaning and purpose’: A qualitative study of pet ownership from the perspectives of people diagnosed with borderline personality disorder - Hayden-Evans, M.; Milbourn, Ben; Netto, J. (EContent Management Pty Ltd, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. Objective: This qualitative study aimed to explore the experiences of pet ownership for adults with borderline personality disorder (BPD) and understand the impacts of pets on their attachments, social connections, and activity participation. Method: Semi-structured interviews were conducted with eight individuals with BPD and analysed using interpretative phenomenological analysis. Results: Five dominant themes emerged: Pets (1) provide meaning and purpose; (2) influence positive emotional attachments; (3) influence positive social connections; (4) promote participation and engagement in meaningful activities; and (5) have therapeutic value. Discussion: Pets provided opportunities for community engagement, social interaction, and participation in meaningful activities, and may aid development of coping skills and secure attachments, inviting further research to confirm the role of pets personally and therapeutically for this population.